THE EVOLUTION OF THE ARTISTIC LANGUAGE OF V. RASPUTIN AND KH. DUSTMUHAMMAD: STAGES AND CHARACTERISTICS (Scientific journal of the Fergana State University, 2025)
The article is devoted to the analysis of the evolution of the artistic language of two prominent 20th-century writers — V. Rasputin and Kh. Dustmuhammad. The study covers the key stages of their creative work and identifies the characteristics of their stylistic development. It examines the distinctive features of the authors' linguistic craftsmanship during various periods of their lives and creative activity, the influence of sociocultural and historical factors on the style and form of their works, as well as the specific syntactic, lexical, and rhetorical structures in their writings. The article investigates how each writer's language reflects changes in world perception, social relations, and personal values. Additionally, the article notes the impact of tradition and innovation on the formation of Rasputin's and Dustmuhammad's artistic language, offering a comparative analysis of these features within the context of world literature.